Exploring Horizons for Domestic Animal Genomics: Workshop Summary - National Research Council (The National Academies Press, 2002)
Recognizing the important contributions that genomic analysis can make to agriculture, production and companion animal science, evolutionary biology, and human health with respect to the creation of models for genetic disorders, the National Academies convened a group of individuals to plan a public workshop that would: (1) assess these contributions; (2) identify potential research directions for existing genomics programs; and (3) highlight the opportunities of a coordinated, multi-species genomics effort for the science and policymaking communities. Their efforts culminated in a workshop sponsored by the U.S. Department of Agriculture, Department of Energy, National Science Foundation, and the National Institutes of Health. The workshop was convened on February 19, 2002. The goal of the workshop was to focus on domestic animal genomics and its integration with other genomics and functional genomics projects.
Keywords: Biology and Life Sciences

Effect of Environment on Nutrient Requirements of Domestic Animals - National Research Council (The National Academies Press, 1981)
Keywords: Biology and Life Sciences

Laboratory Animals: Animals for Research: A Directory of Sources of Laboratory Animals, Equipment, and Materials (The National Academies Press, 1964)
Keywords: Biology and Life Sciences

Laboratory Animals: Part II: Animals for Research (The National Academies Press, 1961)
Keywords: Biology and Life Sciences

Animal Models for Biomedical Research IV: Proceedings of a Symposium (The National Academies Press, 1971)
Keywords: Biology and Life Sciences

Mineral Tolerance of Domestic Animals - National Research Council (The National Academies Press, 1980)
Keywords: Agriculture; Biology and Life Sciences

Animals for Research: A Directory of Sources, Tenth Edition and Supplement - National Research Council (The National Academies Press, 1979)
Keywords: Biology and Life Sciences

Revisiting Brucellosis in the Greater Yellowstone Area - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Brucellosis is a nationally and internationally regulated disease of livestock with significant consequences for animal health, public health, and international trade. In cattle, the primary cause of brucellosis is Brucella abortus, a zoonotic bacterial pathogen that also affects wildlife, including bison and elk. As a result of the Brucellosis Eradication Program that began in 1934, most of the country is now free of bovine brucellosis. The Greater Yellowstone Area (GYA), where brucellosis is endemic in bison and elk, is the last known B. abortus reservoir in the United States. The GYA is home to more than 5,500 bison that are the genetic descendants of the original free-ranging bison herds that survived in the early 1900s, and home to more than 125,000 elk whose habitats are managed through interagency efforts, including the National Elk Refuge and 22 supplemental winter feedgrounds maintained in Wyoming.
Keywords: Biology and Life Sciences; Earth Sciences

The Language of Life: How Cells Communicate in Health and Disease - Niehoff, Debra (The National Academies Press, 2005)
Cooperation requires conversation. Human beings speak to one another. Sounds, scents, and postures allow animals to make their point. While individual cells can’t talk, hiss, growl, or bare their teeth, they nevertheless communicate regularly. Their language is based not on words or gestures, but on chemistry —using molecules where we would use words, constructing sentences from chains of proteins. The cells that make up the bodies of muticellular organisms inform, wheedle, command, exhort, reassure, nurture, criticize, and instruct each other to direct every physiological function, report every newsworthy event, record every memory, heal every wound. And each of those chemical conversations represents an opportunity for scientists and physicians.
Keywords: Biology and Life Sciences; Health and Medicine

In the Light of Evolution: Volume III: Two Centuries of Darwin - National Academy of Sciences (The National Academies Press, 2009)
Two Centuries of Darwin is the outgrowth of an Arthur M. Sackler Colloquium, sponsored by the National Academy of Sciences on January 16-17, 2009. In the chapters of this book, leading evolutionary biologists and science historians reflect on and commemorate the Darwinian Revolution. They canvass modern research approaches and current scientific thought on each of the three main categories of selection (natural, artificial, and sexual) that Darwin addressed during his career. Although Darwin's legacy is associated primarily with the illumination of natural selection in The Origin, he also contemplated and wrote extensively about what we now term artificial selection and sexual selection. In a concluding section of this book, several science historians comment on Darwin's seminal contributions.
Keywords: Biology and Life Sciences; Explore Science

Genetically Engineered Crops: Experiences and Prospects - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Genetically engineered (GE) crops were first introduced commercially in the 1990s. After two decades of production, some groups and individuals remain critical of the technology based on their concerns about possible adverse effects on human health, the environment, and ethical considerations. At the same time, others are concerned that the technology is not reaching its potential to improve human health and the environment because of stringent regulations and reduced public funding to develop products offering more benefits to society. While the debate about these and other questions related to the genetic engineering techniques of the first 20 years goes on, emerging genetic-engineering technologies are adding new complexities to the conversation.
Keywords: Biology and Life Sciences; Agriculture

Science and Technology in Armenia: Toward a Knowledge-Based Economy - National Research Council (The National Academies Press, 2004)
An NRC ad hoc committee analyzed the current status and future development potential of Armenia's science and technology base, including human and infrastructural resources and research and educational capabilities. The committee identified those fields and institutions offering promising opportunities for contributing to economic and social development, and particularly institutions having unique and important capabilities, worthy of support from international financial institutions, private investment sources, and the Armenian and U.S. governments. The scope of the study included both pure and applied research as well as education in science-related fields. The committee's report addresses the existing capacity of state and private research institutions, higher education capabilities and trends, scientific funding sources, innovative investment models, relevant success stories, factors hindering development of the science sector, potential domestic Armenian customers for scientific results and products, and opportunities for regional scientific collaboration. An Armenian language version of the report is also available.
Keywords: Biology and Life Sciences; Industry and Labor

Nutrient Requirements of Nonhuman Primates: Second Revised Edition - National Research Council (The National Academies Press, 2003)
This new release presents the wealth of information gleaned about nonhuman primates nutrition since the previous edition was published in 1978. With expanded coverage of natural dietary habits, gastrointestinal anatomy and physiology, and the nutrient needs of species that have been difficult to maintain in captivity, it explores the impact on nutrition of physiological and life-stage considerations: infancy, weaning, immune function, obesity, aging, and more. The committee also discusses issues of environmental enrichment such as opportunities for foraging.
Keywords: Agriculture; Biology and Life Sciences

Biotechnology: An Industry Comes of Age - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 1986)
Keywords: Biology and Life Sciences

Crocodiles as a Resource for the Tropics - National Research Council (The National Academies Press, 1983)
Keywords: Biology and Life Sciences

Neotropical Primates: Field Studies and Conservation : Proceedings of a Symposium on the Distribution and Abundance of Neotropical Primates - National Research Council (The National Academies Press, 1976)
Keywords: Biology and Life Sciences

Nutrient Requirements of Laboratory Animals,: Fourth Revised Edition, 1995 - National Research Council (The National Academies Press, 1995)
In the years since the third edition of this indispensable reference was published, a great deal has been learned about the nutritional requirements of common laboratory species: rat, mouse, guinea pig, hamster, gerbil, and vole. The Fourth Revised Edition presents the current expert understanding of the lipid, carbohydrate, protein, mineral, vitamin, and other nutritional needs of these animals. The extensive use of tables provides easy access to a wealth of comprehensive data and resource information. The volume also provides an expanded background discussion of general dietary considerations. In addition to a more user-friendly organization, new features in this edition include:
Keywords: Biology and Life Sciences; Agriculture

Medically Assisted Conception: An Agenda for Research - Institute of Medicine (The National Academies Press, 1989)
This book results from a study by a committee of the Institute of Medicine and the National Research Council's Board on Agriculture. The committee examined the scientific foundations of medically assisted conception and developed an agenda for basic research in reproductive and developmental biology that would contribute to advances in the clinical and agricultural practice of in vitro fertilization and embryo transfer. The volume also discusses some barriers to progress in research and ways of lowering them, and explains the scientific issues important to ethical decision making.
Keywords: Biology and Life Sciences; Health and Medicine

Biomedical Models and Resources: Current Needs and Future Opportunities - National Research Council (The National Academies Press, 1998)
Keywords: Biology and Life Sciences

In the Light of Evolution: Volume VII: The Human Mental Machinery - National Academy of Sciences (The National Academies Press, 2014)
Humans possess certain unique mental traits. Self-reflection, as well as ethic and aesthetic values, is among them, constituting an essential part of what we call the human condition. The human mental machinery led our species to have a self-awareness but, at the same time, a sense of justice, willing to punish unfair actions even if the consequences of such outrages harm our own interests. Also, we appreciate searching for novelties, listening to music, viewing beautiful pictures, or living in well-designed houses. But why is this so? What is the meaning of our tendency, among other particularities, to defend and share values, to evaluate the rectitude of our actions and the beauty of our surroundings? What brain mechanisms correlate with the human capacity to maintain inner speech, or to carry out judgments of value? To what extent are they different from other primates' equivalent behaviors? In the Light of Evolution Volume VII aims to survey what has been learned about the human "mental machinery." This book is a collection of colloquium papers from the Arthur M. Sackler Colloquium "The Human Mental Machinery," which was sponsored by the National Academy of Sciences on January 11-12, 2013. The colloquium brought together leading scientists who have worked on brain and mental traits. Their 16 contributions focus the objective of better understanding human brain processes, their evolution, and their eventual shared mechanisms with other animals. The articles are grouped into three primary sections: current study of the mind-brain relationships; the primate evolutionary continuity; and the human difference: from ethics to aesthetics. This book offers fresh perspectives coming from interdisciplinary approaches that open new research fields and constitute the state of the art in some important aspects of the mind-brain relationships.
Keywords: Biology and Life Sciences